An Aggressive Management Strategies for Acute Kidney Transplant Rejection: An Indonesian Tertiary Center Experience - Yudriawan Annas; Trisula Utomo; Tanaya Ghinorawa (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Acute kidney transplant rejection remains a major cause of early graft malfunction worldwide especially in low- and middle-income countries where diagnostic and treatment resources are limited. Global data indicate that 10–20% of recipients experience acute rejection within the first year, with higher rates reported in developing regions. This study examined the clinical attributes and outcomes of intensive therapy approaches for acute graft malfunction at Dr. Sardjito General Hospital in Yogyakarta, Indonesia. A retrospective case series included four adult kidney transplant recipients who developed acute graft malfunction within 30 days of transplantation (2024 - 2025), defined as a >25% rise in serum creatinine and/or oliguria. Demographic data, Doppler ultrasound resistive index (RI), immunosuppressive therapy, therapeutic plasma exchange (TPE), and short-term outcomes were analyzed descriptively. The study comprised three males and one female (aged 23 – 54 years old). All patients showed elevated RI (>0.75). TPE was performed in three cases (75%), resulting in two full recoveries, one partial recovery, and one persistent dysfunction due to combined immunological and surgical complications. Higher RI values were associated with more intensive treatment. These findings suggest that personalized aggressive therapies, such as TPE and intravenous immunoglobulin, may serve as viable salvage options for severe early graft malfunction. In resource-limited settings, Doppler ultrasound provides valuable non-invasive support when biopsy is unvailable. Larger multicenter studies are needed to confirm long-term efficacy and generalizability. Keywords: Kidney Transplantation, Acute Rejection, Therapeutic Plasma Exchange, Doppler Ultrasound, Immunosuppression.